The Polycomb-Dependent Epigenome Controls β Cell Dysfunction, Dedifferentiation, and Diabetes - Lu, Tess Tsai-Hsiu; Heyne, Steffen; Dror, Erez; Casas, Eduard; Leonhardt, Laura; Boenke, Thorina; Yang, Chih-Hsiang; Sagar,; Arrigoni, Laura; Dalgaard, Kevin; Teperino, Raffaele; Enders, Lennart; et al. (Cell Metabolism, 2018)
To date, it remains largely unclear to what extent chromatin machinery contributes to the susceptibility and progression of complex diseases. Here, we combine deep epigenome mapping with single-cell transcriptomics to mine for evidence of chromatin dysregulation in type 2 diabetes. We find two chromatin-state signatures that track β cell dysfunction in mice and humans: ectopic activation of bivalent Polycomb-silenced domains and loss of expression at an epigenomically unique class of lineage-defining genes. β cell-specific Polycomb (Eed/PRC2) loss of function in mice triggers diabetes-mimicking transcriptional signatures and highly penetrant, hyperglycemia-independent dedifferentiation, indicating that PRC2 dysregulation contributes to disease. The work provides novel resources for exploring β cell transcriptional regulation and identifies PRC2 as necessary for long-term maintenance of β cell identity. Importantly, the data suggest a two-hit (chromatin and hyperglycemia) model for loss of β cell identity in diabetes. Lu et al. provide evidence of chromatin dysregulation in type 2 diabetes in mice and humans. Loss of Polycomb silencing in mouse pancreas triggers hyperglycemia-independent dedifferentiation of β cells and diabetes, suggesting a two-hit (chromatin and hyperglycemia) model for loss of β cell identity in diabetes.
CRIS-Team Scopus Importer:2023-03-23
Keywords: cell identity; chromatin; complex diseases; de-differentiation; diabetes; Eed; epigenetic; Polycomb; type 2 diabetes; β cells